Peningkatan Hasil Belajar PPKn dan Keaktifan Siswa Melalui Penggunaan Media Pohon Literasi Kelas V SD YPK Mariarotu - Nurhartina, Andi; Sahara, Desy Putri; Katulung, Marlin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The purpose of this study was to determine the improvement of PPKn learning outcomes through the use of literacy tree media in grade V students of YPK Mariarotu Elementary School. The research conducted was classroom action research (CAR). This research was conducted in two cycles consisting of planning, implementation, observation and reflection which included four meetings. The subjects of this study were 21 grade V students of YPK Mariarotu Elementary School consisting of 11 males and 10 females. Data collection techniques were observation, testing (evaluation), and documentation. The data obtained were then analyzed using quantitative and qualitative descriptive analysis. The results achieved quantitatively were (1) The application of literacy tree media in student activity, response and learning outcomes of grade V students of YPK Mariarotu Elementary School, namely an increase in student activity and courage in each cycle, where student activity in cycle I with an average value of 49.3 in the less active category increased in cycle II to 88.1 in the very active category. (2) Improvement in PPKn learning outcomes and student learning activities in accordance with the results of observations during the classroom action process. The average value obtained by students after taking the final test from cycle I to cycle II after the learning model was applied increased from 59.3 in cycle I to 87.9 in cycle II. The learning completion of PPKn of grade V students of SD YPK Mariarotu also increased. In cycle I, from 9 (42.8%) students to cycle II as many as 18 (85.7%) students achieved learning completion and classical learning completion was achieved, namely 80%. The conclusion is that the literacy tree can improve PPKn learning outcomes and the activeness of grade V students of SD YPK Mariarotu.